Effectiveness of aculief acupressure device on pain perception during local anesthesia in children: A double-blinded study - M Pushpasanthy; Rena Ephraim; Ambili Ayilliath; K B Dhanya (Wolters Kluwer Medknow Publications, 2023)
Aim: The aim of this study was to evaluate the effect of the Aculief acupressure device on the reduction of pain during local anesthesia (LA) in children and to compare it with the cryotherapy technique. Methodology: 20 children of age group between 6 and 9 years, requiring pulpectomy or extraction bilaterally were chosen for the study. After ethical clearance and parental consent, children who were not experienced to prior local anesthesia were chosen for the study. A split-mouth study design was done to avoid bias, and children were divided into two groups. During the first visit cryotherapy application was done on any one side followed by the LA, and during the second visit Aculief acupressure application was done, which was followed by the LA. The objective and subjective evaluation of pain during the LA was carried out and analyzed. Results: The objective perception of pain was evaluated using the Sound-Eye-Motor Scale by an observer who was blinded, and the subjective perception of pain by the Wong-Baker Faces Pain Rating Scale was evaluated by the child patient. The statistical analysis and comparison of values were done using the Wilcoxon signed-rank test. The pain during administration of LA was eliminated after the application of the Aculief acupressure device, and the results were superior to the cryotherapy technique. Conclusion: The Aculief acupressure device can be effectively used to eliminate pain perception while administering LA in children. It is a simple, safe, noninvasive, and effective device and is easy to perform.